Pelatihan Dasar Kepemimpinan: Peran dan Kewajiban Mahasiswa di Universitas Bumigora - Erwin Suhendra; Lela Rahmawati; Baiq Candra Herawati; Gilang Primajati; Wahyu Kamil Syarifaturrahman (LPPM Universitas Bumigora, 2022)
This public service is aim to give knowledge and understanding to students in Universitas Bumigora. This service activity is a student’s management leadership training for basic level. Students’ needs to understand that they have important role and responsibilities in societies and in the college; students are also needs to learn how to manage their selves; to identify leadership identities and to handle conflict. The method used in this public service is there stages; pre-test, workshop and post-test. The participants are students in Universitas Bumigora especially the freshman year. The result obtained is to open horizons of thought that students’ part in the future is important not only to themselves but also to the region, further to our country. Therefore, given knowledge in this student’s management leadership training for basic level expand students understanding in the college and in the community.